Tourism and local self-government on the Dodecanes - Athanasios Stamos; Sasa Kicosev (UTMS Journal of Economics, 2010)
The Southern Sporades Island of Greece, or the Dodecanese as they came to be called around of the 20th century, the islands of the south-eastern Aegean, lie scattered between Crete and Asia Minor. Their two ageold and brilliant civilizations are historically-linked with these islands, which, great or small, inhabited or now uninhabited, number more than twenty, all bearing the traces of human habitation upon them. Today main characteristic of these islands is strong development of tourism.
Keywords: 330; Dodecanese; tourism; local goverment; self-goverment